IL-17 Inhibition: A Valid Therapeutic Strategy in the Management of Hidradenitis Suppurativa - Malvaso, Dalma; Calabrese, Laura; Chiricozzi, Andrea; Antonelli, Flaminia; Coscarella, Giulia; Rubegni, Pietro; Peris, Ketty (Pharmaceutics, 2023)
Hidradenitis suppurativa (HS) is a chronic inflammatory skin disease with a significant negative impact on the quality of life of patients. To date, the therapeutic landscape for the management of the disease has been extremely limited, resulting in a profound unmet need. Indeed, adalimumab, an anti-tumor necrosis factor (TNF)-α monoclonal antibody, is the only approved biologic agent for HS, obtaining a therapeutic response in only 50% of HS patients. Numerous clinical trials are currently ongoing to test novel therapeutic targets in HS. The IL-17-mediated cascade is the target of several biologic agents that have shown efficacy and safety in treating moderate-to-severe HS. Both bimekizumab and secukinumab, targeting IL-17 in different manners, have successfully completed phase III trials with promising results; the latter has recently been approved by EMA for the treatment of HS. The aim of this review is to summarize the current state of knowledge concerning the relevant role of IL-17 in HS pathogenesis, highlighting the key clinical evidence of anti-IL-17 agents in the treatment of this disease.